Efektivitas Gym Ball Exercise terhadap Nyeri Punggung Bawah pada Ibu Hamil Trimester III: Tinjauan Literatur menggunakan PRISMA - Atiqa, Ulfa Diya; Fahruddin, Sri Gunda Fahriana (Fakultas Ilmu Kesehatan, 2025)
Most women in their third trimester of pregnancy experience pain in the lower back, which is generally caused by changes in center of gravity and increased lordosis in posture. The use of gym ball is one intervention that has proven effective in reducing pain during pregnancy, as well as helping to increase the strength of the trunk stabilizer muscle and provide comfort for mother in doing activities. This research aims to find references for gym ball exercises for reducing low back pain in woman during the third-trimester of pregnancy. Literature review was carried out in accordance with the PRISMA (Preferred Reporting Items for Systematic and Meta-Analyses) guidelines, by analyzing 5 research articles, each involving sample sizes ranging from 15 to 28 respondents. Based on the analysis of articles that have been carried out, it appears that gym ball exercises can assist in alleviating lumbar discomfort in women expecting during the final trimester. According to it, all facilities can provide education and gym ball exercises to pregnant women starting third-trimester.